2001
DOI: 10.1523/jneurosci.21-22-08715.2001
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic R-Type Calcium Channels Contribute to Fast Excitatory Synaptic Transmission in the Rat Hippocampus

Abstract: The possibility that R-type calcium channels contribute to fast glutamatergic transmission in the hippocampus has been assessed using low concentrations of NiCl(2) and the peptide toxin SNX 482, a selective antagonist of the pore-forming alpha(1E) subunit of R-type calcium channel. EPSPs or EPSCs were recorded in the whole-cell configuration of the patch-clamp technique mainly from CA3 hippocampal neurons. Effects of both NiCl(2) and SNX 482 were tested on large (composite) EPSCs evoked by mossy and associativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
78
2
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(91 citation statements)
references
References 42 publications
(73 reference statements)
10
78
2
1
Order By: Relevance
“…The properties of the isolated current compare favorably with those reported for R-type calcium current Tsien, 1995, 1997). Previously reported functions for R-type current include the control of neurotransmitter release (Wu et al, 1998;Gasparini et al, 2001), the enhancement of presynaptic plasticity (Dietrich et al, 2003), and calcium entry into dendrites Magee and Johnston, 1995a,b;Magee et al, 1995;Isomura et al, 2002;Yasuda et al, 2003). Our results, demonstrating that R-type current is a critical component in generating the ADP and bursting, identify a novel role of this current in cellular excitability.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…The properties of the isolated current compare favorably with those reported for R-type calcium current Tsien, 1995, 1997). Previously reported functions for R-type current include the control of neurotransmitter release (Wu et al, 1998;Gasparini et al, 2001), the enhancement of presynaptic plasticity (Dietrich et al, 2003), and calcium entry into dendrites Magee and Johnston, 1995a,b;Magee et al, 1995;Isomura et al, 2002;Yasuda et al, 2003). Our results, demonstrating that R-type current is a critical component in generating the ADP and bursting, identify a novel role of this current in cellular excitability.…”
Section: Introductionsupporting
confidence: 64%
“…R-type calcium channels are also modulated by LTP-inducing stimuli, resulting in increased calcium entry into dendritic spines (Yasuda et al, 2003), and they play a role in apoptosis associated with juvenile myoclonic epilepsy (Suzuki et al, 2004). In other cell types, R-type current contributes to neurotransmitter release (Wu et al, 1998;Gasparini et al, 2001) and presynaptic plasticity (Dietrich et al, 2003). Our study is the first to identify R-type currents as an important A mixture of calcium channel antagonists (Mix) 10 M nimodipine with either 100 M -conotoxin GVIA and 100 nM -agatoxin IVA (n ϭ 7) or 10 M -conotoxin MVIIC (n ϭ 7) reduced the tail current.…”
Section: A Novel Role For R-type Calcium Currentmentioning
confidence: 99%
“…Ca 2+ -imaging experiments recently suggested the presence of R-type Ca 2+ channels in a subset of hippocampal mossy fiber boutons [59]. It remains to be shown whether these findings can be confirmed in direct recordings and what role R-type Ca 2+ channels play in mossy fiber synaptic transmission [16,32].…”
Section: Abstract Presynaptic Recording Mossy Fiber Boutons Mossymentioning
confidence: 99%
“…24 The R-type channel also localizes presynaptically and may participate in neurotransmitter release, 32 although its contribution is smaller and varies with brain region. 33,34 With a few exceptions, it has been suggested that calcium channel isoforms are developmentally regulated with N-and R-type common in immature terminals, later favoring P/Q-type in maturity. 34,35 In the CNS, P/Q-type channels are often associated with excitatory synaptic transmission, whereas N-type channels tend to be involved in inhibitory neurotransmission.…”
Section: Ca V 2 Channels Are Critical In Neurotransmitter Releasementioning
confidence: 99%